Effect of Gluten Free Casein Free Diet on Maladaptive Behavior in Autistic Children: Meta-Analysis - Nurul Hakim, Ruliany Yuni; Tamtomo, Didik; Murti, Bhisma (Indonesian Journal of Medicine, 2023)
Background: Children with Autism tend to experience gastrointestinal disorders more often. Interactions between the gut and brain microbiome influence mood and behavior in health and disease. Diet therapy, specifically the gluten and case-free diet (GFCF) is an elimination diet that involves removing certain proteins from the normal diet, such as gluten and casein. The right intervention can change behavior for the better and through the right handling. This study aims to estimate the effect of a case-free gluten-free diet on maladaptive behavior in autistic children, through a meta-analysis of primary studies conducted by previous authors. Subjects and Method:  This study is a systematic review and meta-analysis with the following PICO, population: Autism children, intervention: gluten-free case-free diet, comparison: no case-free gluten-free diet, outcome: maladaptive behavior. The articles used in this study were obtained from three databases, namely PubMed, Google Scholar, and Science Direct, using the search key “Diet Gluten Free Casein Free” OR “NonDiet Gluten Free Casein Free” OR “GFCF” AND “Autism” OR “Autism” AND “Maladaptive” AND “Randomize Controlled Trial” OR “RCT”. The included article is a full-text Randomized Controlled Trial study designed from 2002 to 2022 and reports the mean and SD in multivariate analysis. The selection of articles is done using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.4 application. Results:  A total of 7 randomized controlled trial studies conducted in the Americas, Europe, and Asia were selected for meta-analysis. Autistic children who received casein-free gluten-free had an average score of 0.11 units of maladaptive behavior lower than those who were not given a diet (SMD= 0.11 95% CI= .035 to 0.13; p= 0.360). Conclusion:  The casein-free gluten-free diet has an effect on reducing the risk of maladaptive behavior in children with autism. Keywords:  casein free gluten-free diet, gfcf, maladaptive behavior, autism Correspondence: Ruliany Yuni Nurul Hakim. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A Surakarta 57126, Central Java, Indonesia. Email: Ruliany27@gmail.com. Ponsel +6282124886320. Indonesian Journal of Medicine (2023), 08(03): 286294